Tectonic Evolution of the Active "Chelif" Basin (Northern Algeria) from Paleomagnetic and Magnetic Fabric Investigations - M.E.M., Derder; B., Henry; M., Amenna; B., Bayou; S., Maouche; J., Besse; A., Abtout; H., Boukerbout; M., Bessedik; S., Bourouis; M., Ayache (IntechOpen, 2011)
None